A hybrid rumor detection model derived from a comparative study of supervised approaches - Aothoi, Mehzabin Sadat; Ahsan, Samin; Ahmed, Fardeen (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.